(1-x)PMN-xPT ceramics prepared by conventional and modified columbite route: Effect on electrical properties - Cavalheiro, A. A.; Bruno, J. C.; Zaghete, M. A.; Varela, José Arana [UNESP] (Taylor & Francis Ltd, 2006)
This study aims to demonstrate how the chemical homogeneity of B cations affects the microstructure and electrical responses of (1-x) PMN-xPT ceramics. Two methodologies were employed to synthesize three different compositions, with x assuming the values 0.10, 0.28, and 0.35. If compared to conventional method, the Ti-modified columbite route, which is characterized by higher B cation homogeneity, leads to PMN-PT powders and ceramics with lower content of PNT pyrochlore phase and, for 0.65PMN-0.35PT composition, minor amount of tetragonal phase is found. Conclusively, PMN-PT ceramics obtained by modified route favors B cations homogeneity, enhancing the dielectric, ferroelectric and piezoelectric properties.
Keywords: Ti-modified columbite route; PMN-PT ceramic; electric properties